Psychoactive substances: novel molecular insights and therapeutic potential for Alzheimer's disease - Chonglei Fu; Xuehui Li; Xiaoxing Liu; Yongbo Zheng; Xiangxian Ma; Bo Zhang; Si Chen; Lingming Hu; Sizhen Su; Xiaokun Wang; Jie Sun; Qingqing Yin; et al. (Translational Neurodegeneration)
Abstract Alzheimer's disease (AD) is a major neurodegenerative disorder that causes severe cognitive decline and poses a significant burden on global health systems. Despite extensive research, effective treatments to stop neurodegeneration or promote neuronal regeneration in AD remain elusive. Psychoactive substances as modulators of neurophysiological functions, have received increased attention in research. The main psychoactive agents, such as central nervous system depressants and stimulants, cannabinoids, psychedelics, opioids and ketamine, are being explored for their abilities to enhance learning and cognitive performance and potential neurorestorative functions. In this paper, we review the molecular mechanisms and therapeutic potential of psychoactive substances in AD, in the aim to guide future research directions.